REPRESENTATION OF VIOLENCE IN LEILA S. CHUDORI’S LAUT BERCERITA - Gultom, Sri Ramadhana; Sahri, Zulfan (Universitas Islam Sumatera Utara, 2025)
This study explores the representation of violence in Leila S. Chudori’s novel Laut Bercerita through the theoretical lens of Johan Galtung’s typology of violence—direct, structural, and cultural. Employing a descriptive qualitative method, the research examines how acts of violence are constructed and conveyed through the narrative strategies and language choices of the novel. Findings reveal that violence is not only experienced by the protagonist, Biru Laut, but also by a wider circle of student activists, portraying a collective trauma rooted in Indonesia's New Order regime. The novel encapsulates various forms of violence: physical torture, psychological torment, and functional oppression—all of which are embedded in both the characters' lived experiences and the oppressive sociopolitical systems that surround them. Chudori’s work serves as a literary vehicle to represent silenced histories and resist institutionalized injustice. This research underscores how literature can function as a medium of historical testimony and cultural critique, contributing to the broader discourse on human rights and collective memory. The findings also reinforce Galtung’s theory, affirming its relevance in analyzing representations of systemic and symbolic violence in post-authoritarian literary texts.